Extrarenal Manifestations in Shigatoxin-associated Haemolytic Uremic Syndrome - Matthies, J.; Hünseler, C.; Ehren, R.; Volland, R.; Körber, F.; Hoppe, B.; Weber, L. T.; Habbig, S. (Klinische Pädiatrie, 2016)
Background: Shigatoxin-associated haemolytic uremic syndrome (STEC-HUS) is the most frequent cause of acute kidney injury in children worldwide. Extrarenal manifestations are the main determinants for both, short- and long-term prognosis of patients with STEC-HUS.Patients: 46 patients treated over the last 10 years for STEC-HUS in a single center.Methods: This retrospective study analysed the incidence and outcome of extrarenal manifestations in our cohort of children with STEC-HUS. Risk factors for extrarenal involvement and adverse outcome were assessed by detailed chart review.Results: Eleven extrarenal manifestations occurred in 9/46 patients comprising 8 neurological, 2 gastro-intestinal, and 1 cardiovascular complication. One patient died from cerebral bleeding. Liver transplantation was required in a girl 18 months after HUS due to secondary sclerosing cholangitis. Patients with extrarenal manifestations were significantly younger and presented with higher leucocyte counts and higher alanine aminotransferase levels at admission. Renal replacement therapy was necessary for a longer period than in patients without extrarenal complications.Conclusion: Extrarenal manifestations occurred in about 20% of our patients with STEC-HUS. The identification of risk-factors will help to provide a better management of these patients which might also include novel treatment strategies like complement inhibition.
Keywords: Children; Escherichia coli; Thrombotic Microangiopathy; Dialysis; Eculizumab